2007
DOI: 10.1016/s0210-4806(07)73739-7
|View full text |Cite
|
Sign up to set email alerts
|

Sistema Prolift en la corrección del prolapso genital femenino

Abstract: According to our experience the correction of the female genital prolapse with Prolift system is safe and effective; nevertheless a long follow-up is required to observe the good results in the time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…All 16 patients with preoperative SUI were cured and no patient of the remaining 4 developed incontinence after correction. These results are in accordance those of Solà Dalenz et al who demonstrated the possibility to treat the prolapse and the incontinence simultaneously with two meshes without adding morbidity [18]. We believe that the strategy for management of concomitant SUI improves the results by the restoration of the defective connection between the urethra and the vagina and, therefore, via the reinforcement of the suburethral hammock.…”
Section: Discussionsupporting
confidence: 90%
“…All 16 patients with preoperative SUI were cured and no patient of the remaining 4 developed incontinence after correction. These results are in accordance those of Solà Dalenz et al who demonstrated the possibility to treat the prolapse and the incontinence simultaneously with two meshes without adding morbidity [18]. We believe that the strategy for management of concomitant SUI improves the results by the restoration of the defective connection between the urethra and the vagina and, therefore, via the reinforcement of the suburethral hammock.…”
Section: Discussionsupporting
confidence: 90%
“…Transvaginal sacrospinal cervicopexy using the PROLIFT system has been an effective surgical method for the treatment of apical genital prolapse (7). Nevertheless, certain criticism regarding transvaginal access in the reconstructive treatment of GP using transvaginal Mesh-systems (TVM) exists (8,9) due to the relatively high incidence and severity of complications associated with the use of TVM.…”
Section: Introductionmentioning
confidence: 99%